PERENCANAAN PEMBANGUNAN DESA WISATA NONGKOSAWIT KECAMATAN GUNUNGPATI KOTA SEMARANG - Putri, Restyani Ayu; Hariani, Dyah; Sulandari, Susi (Journal of Public Policy and Management Review, 2013)
According to Law No 32 of 2004 (Local Government) and Law No 25 of 2004 (National Development Planning System), regional development planning must be done in a participatory and starting from the bottom (bottom-up planning) that begins from the village. Similarly with The Planning of Development Nongkosawit Tourism Village, which apply the development plans through a bottom-up planning to be a Tourism Village. The research was conducted in the Village/Urban Village the District of Nongkosawit in Gunungpati of Semarang City. The method used is disqualitative-descriptive method. This research aims to: (1) describe the implementation of development planning (bottom-up planning) Nongkosawit Tourism Village, (2) describe the planning phase of the Nongkosawit Tourism Village, (3) determine the supporting and inhibiting factor on the successful implementation of development planning in Nongkosawit Tourism Village.The results showed that: (1) implementation of development planning (bottom-up planning) Nongkosawit Tourism Village produces 7 priority proposal of tourism village in Musrenbang on the Nongkosawit urban village level, and 3 priority proposal of tourism village in Musrenbang on the Gunungpati district level. (2) Some of the implementation phase of development planning of Nongkosawit Tourism Village has not been done which is determined the structure and manpower requirements, assessed feasibility of projects, developed the input project, feasibility studies, and monitoring and evaluation, the rest of the implementation development has been done well. (3) There are 4 factors that determine the successfull of the implementation of development planning in Nongkosawit Tourism Village. Because every factor has elements that support and inhibit the successful of the implementation of development planning Nongkosawit Tourism Village, so every factor is rated as supporting and inhibiting factors.It can be concluded that the implementation of development planning in Nongkosawit Tourism Village running smoothly either in regulatory or technical implementation. However, to get an maximum results the author gives some recommendations, there are: (1) Nongkosawit must have the high commitment and optimism for being a tourism village (2) The role of village government should be maximized (3) Planners should immediately follow up several stages of the implementation of the plan which has not been implemented (4) People need to be given the regular socialization about tourism village.